The Development of Gross Motor Skills of Upper Grade Students at SD Negeri 1 Dukuh Tengah Maleber is impeded by the implementation of traditional sports. - Prasetyo, Dery; Firmana, Iif (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
This study examines the significance of gross motor development in school-aged children and the frequent disregard by parents of this aspect. Objective. In order to evaluate the efficacy of dodging run training in enhancing students' agility, experimental research was conducted using a pretest-posttest design with a single cohort. Materials and Methods. The data collection method employs a measurement test both before and after the action, followed by data analysis that includes normality tests, homogeneity tests, and hypothesis tests. The objective of this investigation is to determine the beneficial effects of traditional hadangan sports on the development of gross motor skills in upper-class students at SD Negeri 1 Dukuh Tengah Maleber. The development of children's gross motor abilities is believed to be facilitated by hadangan games, which involve movements such as running, jumping, and walking. Results. The outcomes of the data processing procedure are as follows: 1. The treatment process through traditional obstacle sports results in a substantial improvement of gross motor skills, as evidenced by a probability (sig.) of 0.000 <0.05. Consequently, it can be inferred that the implementation of obstacle sports treatment at SD Negeri 1 Dukuh Tengah Maleber has resulted in a significant improvement in gross motor skills. 2. The treatment process has undergone a substantial transformation as a result of the traditional obstacle sports, as evidenced by a tcount value of 8.742 and a ttable value of 2.144. It is possible to infer that tcount exceeds ttable. Conclusion. Therefore, it can be concluded that the implementation of traditional hadangan athletics has resulted in an improvement in gross motor skills among students of SD Negeri 1 Dukuh Tengah Maleber.